New tester strains with improved bioactivation capacity for the Drosophila wing-spot test - Frölich, A.; Würgler, F.E. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1989)
In Drosophila melanogaster new tester strains for the somatic mutation and recombination test (SMART) in the wing were constructed with the aim of increasing the metabolic capacity to activate promutagens. Some aspects of the genetic control of the xenobiotics metabolism in Drosophila are already known. In the DDT-resistant strain Oregon R(R) the RI gene at position 65.0 on chromosome 2 is responsible for the high constitutive expression of cytochrome P-450-dependent activities typical for this strain. Therefore, chromosomes 1 and 2 in the original mwh (multiple wing hairs) and flr 3 (flare 3) tester strains were substituted for chromosomes 1 and 2 from the Oregon R(R) strain. In assays with the model promutagen diethylnitrosamine an increased sensitivity of about 2.5-fold was found for this new set of ‘HB’ strains (‘High Bioactivation (HB) cross’).